Parallel numerical computation of an analytical method for solving an inverse problem - Nachaoui, Abdeljalil; Nachaoui, Mourad; Gasimov, Bayram (Advanced mathematical models & applications, 2021)
We solve the inverse Cauchy problems for the Laplace and Poisson equations using a closed-form regularization analytical solution. The formula is written in the form of series whose terms are integrals. The discretization is done using a Gaussian quadrature, and the finite sum thus obtained is implemented on distributed memory using the Message Passing Interface (MPI). A detailed study of the parallelization procedure is presented.